Aqueous Polymerization of Acrylonitrile with Cerium(IV)- p-Hydroxyacetophenone Redox System - M. Palanivelu; K. E. N. Nalla Mohamed; M. Prem Nawaz (E-Journal of Chemistry)
Aqueous polymerization of acrylonitrile initiated by Ce(IV)/ p-hydroxy acetophenone (Ce(IV) – HAP) was studied in aqueous solution of sulfuric acid at 40 °C. The rate of polymerization was investigated at various concentrations of monomer, initiator, activator, sulfuric acid and the effect of temperature of 30-70 °C range was studied. The rate of polymerization is governed by the expression Rp = Kp [M]1.44 [Ce(IV)] 0.55 [HAP] 0.51. The activation energy of polymerization was found to be 17.9 kJ/mol. A probable mechanism consistent with the observed results is proposed and discussed.